2000
DOI: 10.1046/j.1365-2710.2000.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile-associated diarrhoea in hospitalised patients

Abstract: Patients admitted from NHs are at increased risk of development of CDAD; receiving cefotaxime or cefuroxime axetil (oral form), being elderly and being female are risk factors for the development of CDAD. Treatment of CDAD with oral metronidazole or oral vancomycin gives rise to similar response times and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 40 publications
3
42
0
1
Order By: Relevance
“…40 This analysis led to more robust guidance on the use of antibiotics to be developed and introduced in the study site hospitals in 1995, with a significant revision in 1999 specifically to restrict the use of broad-spectrum cephalosporins in response to an outbreak of CDI, as there was strong association with the use of these agents. 41 All antibiotic usage policies were regularly reviewed and updated. Importantly, it has been emphasized that an approach combining optimal infection control practices with antimicrobial stewardship is required in order to interrupt transmission and successfully control CDI outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…40 This analysis led to more robust guidance on the use of antibiotics to be developed and introduced in the study site hospitals in 1995, with a significant revision in 1999 specifically to restrict the use of broad-spectrum cephalosporins in response to an outbreak of CDI, as there was strong association with the use of these agents. 41 All antibiotic usage policies were regularly reviewed and updated. Importantly, it has been emphasized that an approach combining optimal infection control practices with antimicrobial stewardship is required in order to interrupt transmission and successfully control CDI outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotics such as third generation cephalosporins are accepted as the main risk factors, and antibiotic restriction is the most effective control measure (Starr et al, 2003;Schwaber et al, 2000;McFarland et al, 1999;Al-Eidan et al, 2000). Older age, female gender and a prolonged hospital stay were identified risk factors in hospitalized CDAD patients (Al-Eidan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics such as third generation cephalosporins are accepted as the main risk factors, and antibiotic restriction is the most effective control measure (Starr et al, 2003;Schwaber et al, 2000;McFarland et al, 1999;Al-Eidan et al, 2000). Older age, female gender and a prolonged hospital stay were identified risk factors in hospitalized CDAD patients (Al-Eidan et al, 2000). More recent studies reported the association of the use of proton pump inhibitors within the preceding 8 weeks, the use of nasal feeding tubes and exposure to antineoplastic agents with an increased risk of C. difficile diarrhoea (Cunningham et al, 2003;Komatsu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have found that hospitalacquired infection with C. difficile increases a patient's length of stay by one to three weeks. 2,[5][6][7][8] However, these estimates are potentially biased. First, previous studies have not accounted for the time-varying nature of this infection.…”
mentioning
confidence: 99%